1999
DOI: 10.3758/bf03199732
|View full text |Cite
|
Sign up to set email alerts
|

The role of inhibitory associations in perceptual learning

Abstract: Preexposure to two compound flavors (AX and BX) typically enhances their discriminability: An aversion conditioned to AXwill generalize less to BX,especially if the preexposure regime has involved altemated presentations ofAX and BX rather than presenting all AX trials before BX trials (or vice versa). One possible explanation ofthis finding is that altemating preexposure establishes inhibitory associations between the two unique features A and B, thus counteracting the generalization produced by excitatory as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 24 publications
6
53
2
Order By: Relevance
“…Statistical analysis revealed no significant effects of the order variable: F(1, 11) ϭ 1.29 for the main effect of order, and F Ͻ 1 for the Group ϫ Order interaction. This pattern of results exactly matches those previously reported by Mondragón and Hall's (2002) Experiment 4 (although Bennett, Scahill, Griffiths, & Mackintosh, 1999, reported, in their Experiment 3, a formally equivalent study producing the opposite outcome). The pattern obtained here is consistent with the proposal that conditioning proceeded more readily in the intermixed than in the blocked condition, the difference in associative strength being obscured by a floor effect at the end of conditioning, but becoming evident as extinction occurred during the test trials.…”
Section: Resultssupporting
confidence: 91%
“…Statistical analysis revealed no significant effects of the order variable: F(1, 11) ϭ 1.29 for the main effect of order, and F Ͻ 1 for the Group ϫ Order interaction. This pattern of results exactly matches those previously reported by Mondragón and Hall's (2002) Experiment 4 (although Bennett, Scahill, Griffiths, & Mackintosh, 1999, reported, in their Experiment 3, a formally equivalent study producing the opposite outcome). The pattern obtained here is consistent with the proposal that conditioning proceeded more readily in the intermixed than in the blocked condition, the difference in associative strength being obscured by a floor effect at the end of conditioning, but becoming evident as extinction occurred during the test trials.…”
Section: Resultssupporting
confidence: 91%
“…Thus, although it seems clear that A interferes with X for activation of the outcome representation, it still needs to be explained why the strong activation of the A-O association during the test phase does not produce a response. One possibility could be to assume that an inhibitory association between X and A is acquired during training (because when A is present, X is absent, see Espinet, Iraola, Bennett, & Mackintosh, 1995), and this inhibitory association then prevents responding to the representation of the absent cue, A, which is activated at testing when X is presented (Bennett, Scahill, Griffiths, & Mackintosh, 1999;Mackintosh & Bennett, 1997). Although this explanation was suggested to account for a rather different phenomenon, Matute and Pineño (1998b) suggested that it could plausibly be extended to explain why the strong activation of A did not produce responding at test in the experiments of interference between elementally trained cues.…”
Section: Discussionmentioning
confidence: 99%
“…The rats then received conditioning trials with AX as the conditioned stimulus (CS) and an injection of lithium chloride (LiCl) as the unconditioned stimulus (US). A subsequent generalisation test showed that the rats given the intermixed pre-exposure schedule consumed BX more readily than the rats given the blocked schedule of pre-exposure (see also Bennett et al, 1999;Mondragón and Hall, 2002). This result has been taken to be an instance of perceptual learning-as evidence that alternating pre-exposure to AX and BX engages learning processes that enhance the discriminability of the stimuli.…”
Section: Introductionmentioning
confidence: 98%